Non-steroidal anti-inflammatory drugs and oxidative stress biomarkers in fish: a meta-analytic review - Luiz Henrique Zaniolo Justi; Juliana Ferreira Silva; Manuela Santos Santana; Henrique Aparecido Laureano; Meire Ellen Pereira; Cláudia Sirlene Oliveira; Izonete Cristina Guiloski (Toxicology Reports)
Drug residues have been detected in aquatic environments around the world and non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most used classes. Therefore, it is important to verify the physiological effects of these products on exposed non-target organisms such as fish. Through a meta-analytic review, we evaluated the effects of NSAIDs on oxidative stress biomarkers in fish. Overall, Diclofenac was the most frequently tested drug in the systematically selected studies while acute and hydric exposure types were the most prevalent among these studies. The meta-analysis revealed that (1) chronic and subchronic exposures to NSAIDs decreased catalase (CAT) activity, and acute exposure increased glutathione peroxidase (GPx) activity; (2) hydric exposure increased GPx activity; (3) exposure to low concentrations of NSAIDs increased GPx and superoxide dismutase (SOD) activity; (4) Paracetamol exposure increased GPx and SOD activity and lipid peroxidation levels, but reduced glutathione S-transferase (GST) activity; (5) Diclofenac exposure increased GPx activity. In conclusion, our results demonstrated that fish are sensitive to NSAIDs exposure presenting significant alterations in oxidative stress biomarkers, especially in the GPx enzyme. This enzyme exhibits strong potential as a biomarker of NSAIDs exposure in fish. Paracetamol stood out as the NSAID that altered the largest number of oxidative stress biomarkers, drawing attention to its risk to fish. In contrast, ibuprofen did not change the biomarkers evaluated. These data demonstrate the important impact of emerging contaminants such as NSAIDs on aquatic organisms and the need for strategies to mitigate these effects.